The Role of Nigerian and United States Air Forces in Implementing Nigeria's Foreign Policy Against Boko Haram Terrorism in 2014-2021 - Putri, Faradillah Isnaeni; Pedrason, Rodon; Wenas Inkiriwang, Frega Ferdinand; Wulandari, Adelia (CV RIFAINSTITUT, 2024)
This research analyzes the role of the Nigerian government and United States Air Forces in implementing Nigeria's foreign policy against Boko Haram terrorism from 2014 to 2021. The problem statement focuses on how military cooperation between Nigeria and the US, particularly through air power, supported Nigeria in combating the Boko Haram threat. The study employs a qualitative approach, using secondary data sources such as government reports, academic articles, and official statements. The theoretical framework is based on the concepts of national interest and international cooperation, examining how these factors shaped the bilateral relationship and military strategies. The research concludes that the cooperation between the Nigerian and US air forces significantly contributed to Nigeria's efforts to achieve its national security goals, emphasizing the importance of international collaboration in addressing complex security challenges.